2017
DOI: 10.1161/circresaha.116.308825
|View full text |Cite
|
Sign up to set email alerts
|

Polydom Is an Extracellular Matrix Protein Involved in Lymphatic Vessel Remodeling

Abstract: Polydom affects remodeling of lymphatic vessels in both mouse and zebrafish. Polydom deposited around lymphatic vessels seems to ensure Foxc2 upregulation in lymphatic endothelial cells, possibly via the Ang-2 and Tie1/Tie2 receptor system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
100
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(117 citation statements)
references
References 50 publications
7
100
0
Order By: Relevance
“…Foxc2 expression was decreased in the polydom -/- mice. Those animals lacked maturation of collecting lymphatic vessels and lymphatic valves (522, 727). It was mentioned previously that Notch1 negatively regulates Prox1 expression during LEC specification.…”
Section: Development Of Lymphatic Vessel Networkmentioning
confidence: 99%
“…Foxc2 expression was decreased in the polydom -/- mice. Those animals lacked maturation of collecting lymphatic vessels and lymphatic valves (522, 727). It was mentioned previously that Notch1 negatively regulates Prox1 expression during LEC specification.…”
Section: Development Of Lymphatic Vessel Networkmentioning
confidence: 99%
“…Rescue experiments with bacterial artificial chromosome (BAC) transgenes, as well as mRNA, confirmed that lymphatic defects were due to loss of svep1 function. In parallel, Morooka et al applied genome editing to generate a targeted deletion in zebrafish svep1 , which led to the same defects in thoracic duct formation 10 , further confirming the requirement for this gene in lymphatic development. More careful assessment of the mutant phenotype in zebrafish revealed that early lymphatic specification was unaffected, with Prox1 expression apparent in progenitors in the cardinal vein, although sprouting of these lymphatic progenitors was deficient.…”
mentioning
confidence: 90%
“…As noted above, Morooka et al initially identified Svep1 as a binding partner for integrin α9β1, which itself is required for lymphatic valve morphogenesis 9 . However, svep1 mutant mice show much broader defects in the lymphatic system that those associated with integrin α9 -deficiency 10 , while integrin α9 mutant zebrafish do not recapitulate the svep1 mutant phenotype 11 . These results suggest that Svep1 acts independently of integrin α9 during lymphatic maturation, although a functional interaction during valve formation cannot be ruled out.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Collectively, these results suggest that SVEP1 may have previously unappreciated and multifactorial roles in contributing to CVD. Homozygous Svep1 -/mice die from edema, and heterozygous mice, as well as zebrafish, experience arterial and lymphatic vessel malformations [28][29][30] . Consistent with previous investigations 31 , RNAseq data in a subset of GeneSTAR participants do not indicate expression of SVEP1 in platelets.…”
mentioning
confidence: 99%